Implementation Of MATATAG Curriculum Vis-A-Vis Reading Skill Among Grade 1 Pupils - Imperial, Samantha Grace (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of the MATATAG Curriculum and its influence on the reading and literacy skills of Grade 1 pupils at Guinsangaan Elementary School in Dipolog City, Philippines. Anchored in Vygotsky’s Sociocultural Theory, Piaget’s Theory of Cognitive Development, and the Phonics Theory of Reading, the research explored how structured literacy instruction under the MATATAG Curriculum affects learners’ foundational reading competencies. The study employed a quantitative comparative research design using secondary data from the Comprehensive Rapid Literacy Assessment (CRLA). Respondents included all Grade 1 pupils whose literacy assessment records were available from two academic periods: pupils taught under the old curriculum during School Year 2023–2024 and pupils taught under the MATATAG Curriculum during School Year 2024–2025. Data were analyzed using mean difference analysis and the Independent Samples T-Test. Findings revealed that pupils taught under the MATATAG Curriculum achieved significantly higher literacy scores compared to those taught under the old curriculum. The MATATAG group obtained a mean CRLA score of 29.63, while the old curriculum group obtained a mean score of 15.54, resulting in a mean difference of 14.09. Statistical analysis further showed a significant difference between the two groups, with a computed t-value of 18.144 and a p-value of .000, leading to the rejection of the null hypothesis. The results indicate that the MATATAG Curriculum positively influences the reading literacy performance of Grade 1 pupils through its emphasis on foundational literacy, phonics-based instruction, and learner-centered strategies. The study concluded that the MATATAG Curriculum contributes to improved literacy outcomes among early learners and supports its continued implementation in primary education. It recommends strengthening curriculum implementation, providing continuous literacy intervention programs, and conducting further studies on additional literacy dimensions and long-term curriculum effects. The study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting equitable and effective foundational literacy instruction, and with SDG 10: Reduced Inequalities through its focus on literacy development in rural and under-resourced schools. Its sustainability impact lies in supporting inclusive educational development, strengthening institutional literacy practices, and improving long-term learning opportunities for young learners.
Keywords: Comprehensive Rapid Literacy Assessment; Grade 1 Pupils; Literacy Development; MATATAG Curriculum; Phonics-Based Instruction; Quantitative Comparative Research; Reading Comprehension; Reading Literacy; Rural Education; Sustainable Education